Pengaruh Dosis Kompos Pelepah Kelapa Sawit Terhadap Pertumbuhan Bibit Kelapa Sawit Di Main Nursery Pada Berbagai Jenis Tanah - Sihite, Gabriel; Githa Noviana; Valensi Kautsar (Agro Estate, 2024)
This study was conducted to analyze the effect of composting from oil palm fronds and soil type variations, as well as the interaction of these two factors on the development of oil palm seedlings at the main nursery stage at the Education and Research Garden (KP2) Instiper, Wedomartani Village, Sleman, Yogyakarta. The research method uses a factorial design with two factors arranged in a Complete Random Design (RAL), where the first factor is the dose of palm frond compost consisting of four levels, namely 0 grams as a control, 100 grams, 200 grams, and 300 grams, while the second factor includes three types of soil with different characteristics, namely regosol, latosol, and grumusol. Data analysis was carried out using ANOVA for treatments that showed significant differences. Based on the results of the analysis carried out, there was no significant interaction between the application of oil palm frond compost and soil type on the growth of seedlings in the main nursery, but separately it was found that the application of the highest dose of compost of 300 grams per polybag had a real effect on the growth of oil palm seedlings, while on the other hand, the use of latosol type soil showed a significant positive effect. Especially on the dry weight parameter of oil palm seedlings at the main nursery stage, which indicates that these two factors independently have an important role in optimizing the growth of oil palm seedlings